Actualistic Study of a Dense Concentration of Bone Remains in the Central Plateau of Santa Cruz Province (Argentina) - Marchionni, Laura (2017)
This work analyzes a modern bone concentration at Cueva 7, in Los Toldos archaeological locality, as part of the taphonomic studies that we have carried out in the northeast of the Central Plateau of Santa Cruz province (Argentina). The goal of this work is to identify the actualistic taphonomic patterns that can contribute to a better interpretation of the archaeological sites in caves or rock shelters where piles or dense bone concentrations were registered in the study region. From the identification of different taxonomic, anatomic, mortality, and bone modification patterns in this highly-dense accumulation, we evaluate the possible causes of its formation, and produce actualistic information which may be of use to learn about the different processes that accumulate and scatter zooarchaeological remains in the cave environments of the study area. The results show a monospecific assemblage integrated by no less than 43 Ovis aries individuals whose death was natural. The accumulation is characterized by a natural disarticulation pattern, which appears to be more accelerated in appendicular elements, a homogenous weathering profile with minor differences that may be associated with the microenvironments recorded inside the cave, and the very low incidence of natural agents, where trampling was the highest. This work thus provides valuable actualistic information that can be used as a parameter in the determination of possible natural contamination in archaeological contexts.